1C.02: EVIDENCE FOR A PROGNOSTIC ROLE OF ORTHOSTATIC HYPERTENSION ON SURVIVAL IN A VERY OLD INSTITUTIONALIZED POPULATION. (June 2015) - Agnoletti, D.; Valbusa, F.; Labat, C.; Mourad, J.J.; Benetos, A.
Abstract : Objective: The prevalence and the prognostic role of orthostatic hypertension (OHyperT) in a very elderly population remain unknown. We aimed to investigate the association of OHyperT with cardiovascular morbidity and mortality in a population of elderly institutionalized patients. Design and method: A longitudinal study with 2-year follow-up was conducted on 972 very elderly individuals (mean age [SD] 88[5]) living in nursing homes (223 men) that were able to maintain standing position, included in the PARTAGE study. Socio-demographic characteristics, medical history, chronic diseases (cardiovascular, central nervous system and respiratory), history of falls, comorbidity and medication use were collected. In addition, clinical examination of functional status, cognitive function, blood pressure (BP) and aortic stiffness was performed. BP measurements were repeated at 1 and 3 minutes after standing position. OHyperT was defined as an increase in SBP >20mmHg during the 3 first minutes of standing up. Orthostatic hypotension (OH) was defined as a decrease in systolic BP (SBP) >20mmHg and/or in diastolic BP (DBP) >10mmHg. Cardiovascular morbid-mortality included nonfatal cardiovascular events leading to hospitalization or a specific long-term new treatment as well as death from cardiac, cerebrovascular, and other vascular causes. Results: The population was divided into 3 groups: orthostatic normotension (ONT)(n = 540), OH(n = 157), and OHyperT(n = 275) groups. Mean age was similar and women were 82% in OHyperT versus 69% in OH group. At inclusion, all comorbidities but peripheral arterial disease (11% in OH versus 5% in OHT) were similarly distributed in the three groups. Sitting SBP was higher in OH compared to ONT and OHyperT groups (146[23], 136[21], 136[20] mmHg respectively, all P < 0.001). OHyperT was associated with an increased risk of cardiovascular morbi-mortality adjusted (age and gender) risk-ratio [95% CL] (1.53[1.12–2.08]) compared to ONT. Adjusted (age and gender) risk-ratio of OH versus ONT was directionally increased (1.40[0.96–2.05]). Kaplan-Mayer curves (figure) for cardiovascular morbi-mortality show that ONT group presented higher survival than both OH (HR 1.44[0.95–2.17], P = 0.057) and OHyperT (HR 1.51[1.09–2.08], P < 0.01). Conclusions: In a very old frail institutionalized population, increase in SBP by >20mmHg in upright position has a negative prognostic impact on cardiovascular morbi-mortality. Figure. No caption available.